TOPONYMIC NAMING OF THE MUNICIPALITY OF BRAGANÇA/PA IN THE GENERAL AMAZONIAN LANGUAGE: INTERFACE BETWEEN WORD CREATION AND BRAZILIAN NATIONAL IDENTITY - Jaime Araújo, Marcos (2024)
The secondary objective of this article was to analyze and describe 91 specific elements of Nheengatu toponymy in the municipality of Bragança/PA, selected from Araújo's master's thesis (2019), based on two approaches: the first is based on the new trends in creation of words, by Gonçalves (2016); the second, in French Discourse Analysis, based on the ideas of Maingueneau (1997 and 2008) and Orlandi (2009), with the main objective of understanding the interdiscursive relationships that are evident in the choice of the place name in Nheengatu, since naming was made by a monolingual subject in Portuguese, supported by the text entitled The General Language as a Constructed Identity, by Barros et al. (1996). The geographic elements of Bragança/PA studied were labeled in Portuguese, based on borrowings from Nheengatu, evidencing a stimulus from nationalist thought, belonging to the first generation of the Brazilian romantic movement. This phenomenon allows not only to frame the artistic-literary movements in the set of new trends of lexical expansion in the morphology of current Portuguese, but also to exalt the historical constitution of defense to the formation of a Brazilian National Identity.   Keywords: Toponymic Naming. Nheengatu. Loan. Romantic Movement. National Identity. Morphology.